Geography of Japan (Teikoku-Shoin, 1980)
With the Pacific Ocean to the east, the Sea of Japan to the west and the East China Sea to the south, Japan is an archipelago comprised of four major island and 6,800 smaller islands. Covering about 145,856 square miles (378,000 square kilometers), Japan is slightly larger than the United Kingdom, slightly smaller than California, approximately the same size as Germany, Finland, Vietnam, or Malaysia, and one twenty-fifth the size of the United States. The nearest countries are Korea (about 100 miles to the west), Russia and China. Japan is divided into state-like 47 prefectures. The islands of Japan make up less than 15 percent of Japan's total territory. Most of its territory is in the sea. In addition to the 200 nautical miles (370 kilometers) of ocean that Japan can also claims around the main islands according to the 1982 United Nations Convention of the Law of the Sea it can also claim 200 nautical miles around far flung Japanese islands that extend from near Taiwan and China to far out in the Pacific Ocean.